Does the FICA [Financial Intelligence Centre Act] legislation compromise the unique relationship between attorney-client and is there a conflict? - Dajee, Vimal Victor (Department of Public Law, 2023)
Despite being relatively quite far down the long road to democracy, South Africa did not have any money-law laundering legislation. International pressure from organisations such as the Financial Action Task Force [FATF], the Organisation for Co-operation of Development [OECD] and Asia Pacific Group on Money-Laundering [APG], World Bank, and Interpol has resulted in a new jurisprudence. Since its introduction in 2002, the Financial Intelligence Centre Act, Act 38/2001 (hereinafter referred to as FICA, or 'The Act') has also brought about many perplexing conundrums - one of which being whether amongst other time-consuming and cumbersome obligations imposed by 'The Act' - whether, in fact, the whole relationship between a legal advisor will be severely compromised. In this paper, I shall propose to discuss whether the introduction of FICA legislation creates conflict in the relationship between an attorney and his/ her client. The use of the word 'relationship' postulates and pre-supposes commitment of the attorney to his/her client. To whom does the attorney now owe 'allegiance'? Has the promulgation of the FICA legislation invaded the sanctity and solemnity of the unique relationship between attorney and client? I shall now endeavour to set out what the attorney-client professional privilege is, as well as what the rationale is for the existence of the privilege, and also examine possible consequences that have resulted from the introduction of the FICA legislation as well as constitutional implications.